Research on Flow Characteristics of Ultra-high Pressure Impinging Stream Micro-generator - LI Guang-ji; LU Zheng-wen (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Design a new dynamic ultrahigh pressure structure in this article, This structure include three main zones. Simulate and analyze flow characteristics of three zones in details, providing the basis for the design of micro-size structure with ultra-high pressure. Liquid has gone through three broken and decentralized processes in micro-channels zone、impacting wall zone and flow impinging each other zone, find rule of mirror distribution in impinging zone. According to which, obtain the structure is reasonable. The fresh red wine is experimented, verifying that to obtain the same effect, dynamic ultrahigh pressure method greatly reduce energy consumption than ultra-static pressure. Further put forward and verifying a new method that is combining static and dynamic ultrahigh pressure method, can use a relatively lower pressure to get higher pressure treatment effect. DOI: http://dx.doi.org/10.11591/telkomnika.v11i4.2390